2016
DOI: 10.1007/s11367-016-1045-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative cradle-to-gate life cycle assessment of three concrete mix designs

Abstract: Purpose The concrete industry faces challenges to create concrete mix designs that reduce negative environmental impacts but also maintain high performance. This has led to 'greener' cementitious materials being developed which can decrease the use of traditional Portland cement (PC). This study intended to carry out a 'cradle-to-gate' life cycle assessment (LCA) on concrete mix designs containing different cementitious blends. Methods The aim of this study was to obtain the overall environmental impact, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(59 citation statements)
references
References 35 publications
1
45
0
1
Order By: Relevance
“…Tait et al analyzed the overall environmental impact, with a particular focus on carbon dioxide (CO 2 ) emissions of three concrete mix designs: CEM I (100% PC content), CEM II/B-V (65% PC content, 35% Fly Ash (FA) content) and CEM III/B (30% PC content, 70 % ground-granulated blast-furnace slag (GGBS) content) [7].…”
Section: Review Of Environmental Impact According To Concrete Productionmentioning
confidence: 99%
“…Tait et al analyzed the overall environmental impact, with a particular focus on carbon dioxide (CO 2 ) emissions of three concrete mix designs: CEM I (100% PC content), CEM II/B-V (65% PC content, 35% Fly Ash (FA) content) and CEM III/B (30% PC content, 70 % ground-granulated blast-furnace slag (GGBS) content) [7].…”
Section: Review Of Environmental Impact According To Concrete Productionmentioning
confidence: 99%
“…Furthermore, LCA requires detailed and historical data to measure existing wind farms' performances which is difficult at the early design stage when there is very little concrete information and data available (Cheung et al, 2011). Nevertheless, the advantages of the LCA approach do come with uncertainty analysis and ecological footprint evaluation (Tait and Cheung, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Design engineers should focus on selecting the proper material for new components in the product design and development stage, which will help decide the manufacturing process and other factors influencing the reduction of environmental impact [20,21]. By reducing the environmental impact of a component during the early stages of product development implies the product will have superior end of life impact over the environment [22] …”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that a change in material has higher influenced over the manufacturing process in reducing the environmental impact. Ribeiro et al [21] compared an original multi-material car component to the current component by analysing the environmental impacts throughout their life cycles. The component is part of the automotive brake system and the current component includes a new multi-material injection moulding process and the consumption of recyclable materials.…”
Section: Literature Reviewmentioning
confidence: 99%